An approach to the regulation of banking foundations (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
This paper examines the legal framework for banking foundations in the context of how they have been regulated by the recent Law 26/2013, December 27th,of saving banks and banking foundations. This recently regulation establishes in Title II a new element in the Spanish legal system that has substantial importance for the financial system because these foundations established in reality have effective control over the banks due to the high percentage of share capital that the banking foundations hold in these banks.
Keywords: banking foundation; saving bank; transformation; supervision and control.